“El entorno familiar y su incidencia en la motivación escolar. Estudio de caso en el sexto año de educación básica del Centro Educativo Intercultural Bilingüe “José Francisco Aigaje” de la comunidad lote cuatro, cantón Cayambe, provincia de Pichincha” - Naranjo Aucancela, Matías (2013)
The family environment is the source of all human groups. At first human groups are small and. Limited to a few individuals united by ties of kinship these groups gradually grow. Larger structures need to defend themselves from other groups that may pose a threat to the dominance of a certain territory. These groups begin to establish them more complex relationships. That family is among people "with different ways of thinking, customs, forms of organization, values, reaching only strengthened when they are known", is a reality that is evident in our society today, there is the migration of the rural to urban areas, which for various reasons, such as education, employment, etc.., with this in search of a better way of living, so that a family can encounter on this path, with the advantage of consolidation, as clearly points out the author, when known between these two characters that will form a family. So with different customs and traditions that bind two different families to make a home where they mate over the years and the experience of the couple is constructed to train new people. With responsibility we must comply with the rules established in the family, as we noted some authors on this